The right to strike in the сase-laqw of the European Court of Human Rights: evolution of legal approaches - Otovchyts, Serhii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article deals withs the decisions of the European Court of Human Rights, which reveal the evolution of the court’s approaches to understanding the right to strike. It is noted that an important role in the formation of approaches to the interpretation and understanding of the right to strike in the context of Article 11 of the Convention for the Protection of Human Rights and Fundamental Freedoms was played by such decisions of the ECHR as: Unison v. United Kingdom, Wilson, National Union of Journalists and Others v. United Kingdom, Demir and Bayakara v. Turkey, Energy Yapi-Yol v. Turkey, Norwegian Confederation of Trade Unions and Norwegian Transport Workers Union v. Norway, Gumpert and others v. Germany. The conducted analysis of the ECHR decisions demonstrated the evolution of approaches to understanding the right to strike: from its perception as an indirect tool for protecting professional interests to its recognition as an integral part of the fundamental right to freedom of association. It is noted that, based on the fact that the right to strike is not enshrined in Article 11 of the Convention, the European Court of Human Rights in its decisions formulated the legal position that the right to strike is protected by Article 11 of the Convention, is an important tool for the trade union to protect its interests and the professional interests of its members. The European Court of Human Rights also formulated a position on the need to ensure a balance between the realization of the right to strike and the restriction of this right by the state, since the right to strike is not an advantage, not absolute, and therefore certain conditions and restrictions may apply to it. However, any restriction must be justified, that is, it must be provided for by law, pursue one or more legitimate goals and be necessary in a democratic society to achieve goals clearly formulated and predictable.